Uterovaginal Packing as Treatment in Primary Postpartum Hemorrhage in Patan Hospital - Pradhan, Binita; RC, Laxmi; Sharma, P; Singh, Alka (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: To study the effectiveness of uterovaginal packing in the management of primary postpartum hemorrhage (PPH). Methods: This is a retrospective study conducted in Patan hospital, Lalitpur from January 2009-2011. Patients included in the study were those with intractable hemorrhage not responding to oxytocics. Exclusion criteria included cases of PPH due to trauma. Packing was done using approximately six inches sterile gauze soaked with povidine iodine packed into the uterus from the uterine fundus up to the vaginal canal. The packing is removed after 48 hours of insertion or earlier in cases of failure to control hemorrhage. Results: There were 46 cases of uterovaginal packing for primary PPH. Uterine atony was the commonest cause of packing. Uterovaginal packing was successful in 39(84.7%) cases. Conclusion: Uterovaginal packing is safe, easy and quick procedure to manage primary PPH. It is beneficial in cases of PPH due to atony thereby conserve the uterus.